Post-Operative Outcomes of Radiological and Histopathological Findings after Hydroxyapatite and Allogenic Bone Graft among Jaw Cyst Patients: A Randomized Clinical Trial - Mamun, Showkat; Haider, Ismat Ara; Nasiruddin, -; Rahman, Tarin; Rubel, ATM Tarifuzzaman; Diba, Farah (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Post-surgical outcomes of jaw cyst is very crucial. Objective: The purpose of the present study was to observe the radiological and histological finings as postoperative outcomes after hydroxyapatite and allogenic bone graft among jaw cyst patients. Methodology: This single centre, parallel, randomized clinical trial was conducted in the Department of Oral and Maxillofacial Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July 2006 to June 2008 for a period of two (02) years. Patients presented with radicular and dentigerous cyst with the size of the lesion between 2 cm to 7 cm. in diameter and relatively non infected cystic lesion were selected as study population. The study population were divided into two groups designed as group A treated with hydroxyapatite alloplastic material and group B treated with allogenic-bone graft after enucleation of the cystic lesion. The standard surgical procedure was to be performed meticulously in sterile environment. Post-operative radiograph were taken after one month, three months and six months. Histopathological examination was done after six month of operation which was done in the department of Pathology, BSMMU. Scintigraphic examination was performed after 6 months of the operation to evaluate the viability of the bone graft in the graft site. Result: A total number of 28 patients were recruited for this study of which 14 patients were treated with hydroxyapatite crystals bone graft in group A and 14 patients were treated with allogenic bone graft in group B. The age of patients of both groups ranged between 14 and 58 years. In histopathological examination marked presence of cementing line, woven bone and osteoblast cell was found in patients who were grafted with hydroxyaptite and this had indicated good osteoblastic activity. Increased technetium-99m labeled diphosphonate uptake was found in the patient with allograft. There was a smaller lesion diameter of hydroxyapatite group in comparison with allogenic bone graft group which had indicated comparatively better healing than that of the hydroxyapatite group. Conclusion: In conclusion hydroxyapatite alloplastic material has better radiological and histopathological outcomes than allogenic bone graft after surgery of jaw cyst. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 48-53